Олон улсын харилцааны ахисан түвшний судалгааны онол-арга зүйн зарим асуудал (Journal of International Studies, 2015)
Энэхүү өгүүлэлд олон улсын харилцааны ахисан түвшний судалгаа гэж юуг хэлэх вэ, үүнд улс төрийн шинжлэх ухааны үндсэн категориуд арга зүйн ямар ач холбогдолтой тухайд өгүүлэх болно. A Key Issues in Advanced International Studies: Methodological PerspectivesAbstracts: The categories of political science has most important in advanced international studies. This article talks about a key issues in advanced international studies and their methodological perspectives. Keywords: Advanced studies, international relations, political science, category, special, generally and specially, quantitative and qualitative, contents and forms, essence and visible, casus foederis and consequently, inevitably and unintentionally, possibility and reality, etc.